The development of two novel interhemispheric transfer time tasks and application within a pilot paediatric moderate severe traumatic brain injury cohort - Kordom, Kelly (Division of General Surgery, 2025)
Introduction: Children are particularly vulnerable to injuries sustained during and following moderate or severe traumatic brain injury (TBI) as it can interrupt normal childhood development. Our ability to assess functional outcomes in the post-acute phase of injury is still limited, but imperative for appropriate prognosis and allocation of resources for rehabilitation. Advanced MRI techniques such as diffuse tensor imaging have shown that moderate-severe TBI often results in compromised white matter integrity and has been associated with poor neurocognitive outcomes in children. The corpus callosum is the main commissural region of the brain and one of the most widely reported regions of injury during TBI. Interhemispheric transfer time (IHTT) has therefore been suggested to assess the functional integrity of the corpus callosum. Aim: In this study we aimed to explore the development of two novel electroencephalogram (EEG) based IHTT tasks by investigating the reliability of the measured IHTTs and their feasibility for use in young children who had sustained a TBI. Methods: Two IHTT tasks were developed on MATLAB; a simple motor task and a non-motor task. Both tasks consisted of checkerboard visual stimuli presentation to evoke visual event related potentials (ERPS) on an EEG recording. An adult cohort was recruited to perform these two tasks on a laptop while an EEG was recorded to ascertain if the tasks were effective in producing visual ERPs, and to assess the test-retest and interrater reliability of the two tasks. Reliability was assess using the Intraclass Correlation Coefficient (ICC). Once assessment was complete in the adult cohort, six paediatric moderate-severe TBI patients were recruited to evaluate if the tasks were feasible and appropriate for a young paediatric TBI cohort. Similarly, they were required to perform both the motor and non-motor IHTT tasks on a laptop while an EEG was recorded. IHTTs for both cohorts were measured by calculating latencies of ERP components. Results: All adult participants were able to carry out the tasks with minimal difficulty. The EEG recordings show that the tasks effectively produced ERPs at the occipital and parietal sites. For IHTTs measured from the occipital sites, the calculated IHTTs provided high test-retest reliability for the motor task and moderate test-retest reliability for the non-motor task. Overall moderate inter-rater reliability between the motor and non-motor tasks was also calculated for IHTT measured at the occipital sites. All ICC test-retest and inter-rater reliability values for the IHTT calculated from the parietal sites were considerably low. In our paediatric TBI cohort all participants were able to complete both tasks, however IHTT could not be calculated from the motor task in 50% of the patients due to excessive movement. IHTT could be measured from the non-motor tasks for all patients. Conclusions: The high test-retest reliability for the motor tasks indicates that the IHTT measures are reproducible and independent of the task and EEG set-up. The moderate reliability values for the non-motor tasks are promising and also suggests that further investigation is required to assess what test conditions could improve the ICC scores of the non-motor tasks. The non-motor task served as a better option to calculated IHTT in the paediatric TBI cohort, and indicates that the current motor task may still not be simple enough for the young paediatric TBI population. The non-motor task seems to be a promising tool to measure IHTT in young patients, especially in individuals with cognitive, physical and behavioural limitations following TBI.